Generation and Characterization of Novel Bioactive Peptides from Fish and Beef Hydrolysates - Mohamed Abdelfattah Maky (MDPI AG, 2021)
Bioactive peptides were successfully produced from fish (Gadidae) and beef skeletal muscles after being hydrolyzed for 8 h with pepsin. Subsequently, they were purified using a Sep-Pak C18 cartridge and reversed-phase high-performance liquid chromatography (RP-HPLC). The molecular weights of pure fish and beef peptides were determined to be 2364.4 and 3771.8, respectively. According to Edman degradation, the fish peptide was composed of 21 amino acid residues (F21), while the beef peptide was composed of 34 amino acid residues (B34). F21 and B34 displayed angiotensin-converting enzyme inhibitory activity with a half maximal inhibitory concentration (IC50) values of 7.3 µg/mL and 5.8 µg/mL, respectively. F21 exhibited antioxidant activity with an IC50 value of 389.9 µg/mL, whereas B34 exhibited no antioxidant activity. Moreover, F21 and B34 displayed antimicrobial effects against a wide spectrum of food-borne pathogens and spoilage bacteria. Bioactive peptides derived from muscle proteins are a promising strategy for the production of functional food materials and safe food preservatives.